Fibrosis in low-grade follicular lymphoma – a link to the TH2 immune reaction. Issue 5 (4th May 2017) - Lohneis, Philipp; Wienert, Stephan; Klauschen, Frederick; Anagnostopoulos, Ioannis; Jöhrens, Korinna
Abstract: There is evidence from studies on fibrotic diseases that a TH2 polarized immune response, characterized by the production of cytokines like IL-4, IL-5, and IL-13 is important for fibrosis development. Data concerning the role of TH2 polarized immune response for fibrogenesis in lymphomas are scarce. Using immunohistochemistry, we investigated paraffin embedded tissue specimens of 58 follicular lymphomas (FL) grade 1/2 with and without fibrosis. In FL with fibrosis, we detected more interfollicular GATA-3 positive lymphocytes and a shift towards a TH2 immune response. In areas of fibrosis, which were enriched with myofibroblasts, we observed a polarization of macrophages towards a M2 phenotype with expression of CD163. Our results hold some evidence that a polarization of the adaptive immune system towards a TH2 immune response in the tumor microenvironment is associated with increased fibrosis, which may indicate its functional relevance for either development or maintenance of fibrosis in FL.